The Timeliness of Financial Reporting on Food and Beverage Companies in Indonesia - Kumalasari, Putu Diah; Endiana, I Dewa Made (First Ciera Publisher, 2023)
The timeliness of financial report publication is the period for announcing audited financial reports to the public, which can be determined using the publication date of the financial reports. This research aims to examine the effect of company size, company age, profitability, leverage, and size of the board of commissioners on the timeliness of financial report publication of food and beverage companies listed on the Indonesia Stock Exchange in 2020-2022. The total number of observations was 84 data. The data analysis technique used in this research is the logistic regression analysis. The result of this research indicates that the variable size of the board of commissioners has a positive effect on the timeliness of financial report publication. Meanwhile, the variables of company size, company age, profitability, and leverage do not affect the timeliness of financial report publication.